2022
DOI: 10.1371/journal.pone.0261624
|View full text |Cite
|
Sign up to set email alerts
|

One-year in: COVID-19 research at the international level in CORD-19 data

Abstract: The appearance of a novel coronavirus in late 2019 radically changed the community of researchers working on coronaviruses since the 2002 SARS epidemic. In 2020, coronavirus-related publications grew by 20 times over the previous two years, with 130,000 more researchers publishing on related topics. The United States, the United Kingdom and China led dozens of nations working on coronavirus prior to the pandemic, but leadership consolidated among these three nations in 2020, which collectively accounted for 50… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
(53 reference statements)
2
13
0
Order By: Relevance
“…Exploring COVID‐19 related articles and non‐COVID‐19 related articles published in each of the first 6 months of 2016–2020, Aviv‐Reuven and Rosenfeld (2021) found that international collaboration diversity that was measured by the number of collaborating countries was lower than in non‐COVID‐19 papers and than previous years. Similar findings of the shrink of international collaboration and team size were obtained in a few other studies (Homolak et al, 2020; Wagner et al, 2021). The reduction in team size and international collaboration could be due to the declining time to spend on research (Myers et al, 2020), the complexity of conducting international studies (Aviv‐Reuven & Rosenfeld, 2021), physical and political obstacles (Cai et al, 2021), and high costs for searching and coordination (Fry et al, 2020b).…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…Exploring COVID‐19 related articles and non‐COVID‐19 related articles published in each of the first 6 months of 2016–2020, Aviv‐Reuven and Rosenfeld (2021) found that international collaboration diversity that was measured by the number of collaborating countries was lower than in non‐COVID‐19 papers and than previous years. Similar findings of the shrink of international collaboration and team size were obtained in a few other studies (Homolak et al, 2020; Wagner et al, 2021). The reduction in team size and international collaboration could be due to the declining time to spend on research (Myers et al, 2020), the complexity of conducting international studies (Aviv‐Reuven & Rosenfeld, 2021), physical and political obstacles (Cai et al, 2021), and high costs for searching and coordination (Fry et al, 2020b).…”
Section: Introductionsupporting
confidence: 88%
“…The lack of time and resources available for effective and timely responses made it difficult to push coronavirus research forward by either individual or intra‐country efforts (Fry et al, 2020b). The sharing of knowledge, data, and other resources became more essential than ever, which required collaboration among scientists, organizations, and countries (Cai et al, 2021; Wagner et al, 2021). Additionally, the information processing model also argues that scientists could access a broader scope of information and diverse ideas by collaborating with others and thus produce more novel ideas (Harrison & Klein, 2007; Lee et al, 2015; Pieterse et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, more than 130,000 scientific articles concerning the SARS-CoV-2 virus were published, while the number of researchers studying coronaviruses increased by approximately 500% on a year-toyear basis. 2 Although such a surge was necessary given the speed of spread of the COVID-19, the scientific community must maintain scientific standards and research integrity, 3 and the number of published scientific papers raises doubts about their quality. 4 The increase in the number of publications was largely driven by in silico research aimed at drug refurbishment and discovery.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The scientific community responded in an unprecedented way with a common goal to find an effective form of treatment and prevention against this virus. In 2020, more than 130,000 scientific articles concerning the SARS-CoV-2 virus were published, while the number of researchers studying coronaviruses increased by approximately 500% on a year-to-year basis . Although such a surge was necessary given the speed of spread of the COVID-19, the scientific community must maintain scientific standards and research integrity, and the number of published scientific papers raises doubts about their quality …”
Section: Introductionmentioning
confidence: 99%